Effects of Carbon Dioxide Therapy on Skin Wound Healing - José Prazeres; Ana Lima; Gesiane Ribeiro (Biomedicines)
Promoting rapid healing is a concern in skin wound treatment, as the increased pain and the loss of functional ability when wounds become chronic create a complex problem to manage. This scoping review aimed to explore the literature and synthesize existing knowledge on the therapeutic use of CO2 in treating cutaneous wounds. The literature was selected using previously defined inclusion and exclusion criteria, and 22 articles were selected for data extraction. The most researched type of injury was chronic wounds located on the extremities of the limbs. Carboxytherapy was performed in five different ways: subcutaneous, intradermal, or intralesional injections; in hot water baths with temperatures ranging from 30 to 42 °C; transcutaneous application; intra-abdominal insufflation; and a paste for transcutaneous local application. The main effects of CO2 therapy described were as follows: improved blood flow and local oxygenation, reduction of the inflammatory process, increased collagen production, and improved clinical aspects of wounds, with faster healing. Carboxytherapy can be considered a good alternative for treating skin wounds, although further studies should be pursued to elucidate its molecular mechanisms and enhance its efficacy.